Summary report (North-South Center FloridaUS, 1992)
Suggests that for SMEs to compete successfully, along with larger enterprises, they need inter alia, to actively push for modern and efficient infrastructure; macro economic stability; greater access to information; training and reader access to capital and credit. Identifies sources of assistance available to SMEs and indicates ways in which SMEs can grow focussing on international and governmental support.
DC